Analisis Mikrobiologi terhadap Bekasam Ikan Nila: Potret Bakteri dalam Produk Fermentasi Tradisional - Isnaini Yulia Lestari; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Bekasam is a traditional Indonesian fermented product made from tilapia (Oreochromis niloticus) through a spontaneous fermentation process with the addition of rice and salt. This fermentation process encourages the growth of various microorganisms, especially bacteria, which play a role in the formation of flavor, aroma, and natural preservation of the product. This study aims to observe the microbiological characteristics of bekasam tilapia through colony observation on agar media and microscopic staining using crystal violet and safranin. Macroscopic observations showed the presence of microbial colonies that were round, cloudy white, with a smooth surface and even edges. These colony characteristics indicate good microbial growth on agar media. Microscopically, the bacteria observed in bekasam samples had an irregular distribution, forming aggregates that absorbed intense purple and pink colors. Crystal violet staining gave a purple color to gram-positive bacteria, while safranin gave a pink color to gram-negative bacteria. These findings indicate that bekasam contains an active microbial community that plays a role in the fermentation process. This microbial community can be observed visually through simple staining that provides an overview of the types of bacteria involved in the fermentation process. Microbiological analysis such as this is crucial for understanding the fermentation dynamics of traditional food products like bekasam. Thus, this study provides deeper insight into the microorganisms involved in bekasam production, as well as the importance of monitoring microbiological quality in the manufacturing process of traditional fermented products. Furthermore, the diversity of microbes involved in bekasam fermentation can affect product quality and consistency. Therefore, monitoring the dominant bacterial species during the fermentation process is crucial for maintaining bekasam quality, including its taste, texture, and safety for consumers.